Noise and Leak Handling in Main Cooling Sea Water Pump in MV. DK 03 - Mustholiq; Kensiwi, Fitri; Setiawan, Kemal Joy (RSF Conference Series: Engineering and Technology, 2023)
Auxiliary machinery on board is one of the supports in the smooth operation of the ship. Noise and leakage occur in the main cooling sea water pump in MV. DK 03 will hinder the shipping process. The main cooling seawater pump is one of the pumps on board that functions to drain or transfer seawater to the ME plate cooler as a fresh water cooler jacket cooling ME. This study was conducted to determine the causes of noise and leaks in pumps, the impact that occurs due to noise and leaks in pumps, and efforts that can be made to overcome noise and leaks in the main cooling seawater pump. Researchers use qualitative descriptive methods, triangulation of observations, interviews, and literature studies. Researchers identified the causative factors, impacts, and treatments carried out related to the causes of noise and leaks in the main cooling seawater pump. Researchers will also use data analysis techniques methods Software, Hardware, Environment, and Liveware, which can be referred to as the SHEL model. The results obtained from this study show that the cause of noise and leakage in the main cooling seawater pump is caused by damage to the pump foundation and affect the shaft impeller and other components on the main cooling seawater pump, with the damage having an impact on the freshwater cooling process on the main engine. Handling carried out to prevent this is to carry out maintenance according to PMS (plan maintenance system) replace ship spare parts with standards in accordance with the manual book and carry out operations according to the manual book.